Is the adiposity-associated FTO gene variant related to all-cause mortality independent of adiposity?: meta-analysis of data from 169,551 Caucasian adults - Zimmermann, Esther; März, Winfried (Obesity reviews, 2015)
Previously, a single nucleotide polymorphism (SNP), rs9939609, in the FTO gene showed a much stronger association with all-cause mortality than expected from its association with body mass index (BMI), body fat mass index (FMI) and waist circumference (WC). This finding implies that the SNP has strong pleiotropic effects on adiposity and adiposity-independent pathological pathways that leads to increased mortality. To investigate this further, we conducted a meta-analysis of similar data from 34 longitudinal studies including 169,551 adult Caucasians among whom 27,100 died during follow-up. Linear regression showed that the minor allele of the FTO SNP was associated with greater BMI (n = 169,551; 0.32 kg m−2; 95% CI 0.28-0.32, P < 1 × 10−32), WC (n = 152,631; 0.76 cm; 0.68-0.84, P < 1 × 10−32) and FMI (n = 48,192; 0.17 kg m−2; 0.13-0.22, P = 1.0 × 10−13). Cox proportional hazard regression analyses for mortality showed that the hazards ratio (HR) for the minor allele of the FTO SNPs was 1.02 (1.00-1.04, P = 0.097), but the apparent excess risk was eliminated after adjustment for BMI and WC (HR: 1.00; 0.98-1.03, P = 0.662) and for FMI (HR: 1.00; 0.96-1.04, P = 0.932). In conclusion, this study does not support that the FTO SNP is associated with all-cause mortality independently of the adiposity phenotypes.